Conceptualizing Basic Psychological Needs (BSPN) and motivation regulations as antecedents for guided teachers’ work commitment and satisfaction - Idrus, Norlida; Ahmad, Nor Aniza; Zakaria, Noor Syamilah (Human Resource Management Academic Research Society, 2020)
Guided teachers in Malaysia is carefully selected by the school, district education agency and the state education department. The selection is based on their low teaching competency. The guided teachers or known as GDB will be guided through mentoring by the School Improvement Specialist Coach (SISC+). It is found that amongst the important element that determine teachers’ competency are work commitment and satisfaction. Although the guided teachers programme has been conducted for 6 years (2014-2020), but the current literatures only focusing on the mentoring and the teachers’ perception on the SISC+. There is still limited study that focusing on the GDB work commitment and satisfaction after receiving mentoring from the SISC+ even though those two elements are imperatives to be studied. Henceforth, the aim of this article is to provide arguments on potential solutions to tackle on the said problem. It is argued that motivational capacity is paramount in enhancing work commitment and satisfaction. This study embarks to describe and conceptualize the important of Self-Determination Theory (SDT) in affecting both the work commitment and satisfaction of the guided teachers. It includes the discussion on Basic Psychological Needs (BSPN) and Motivational Spectrum. Initially, the article will discuss on the guided teachers work commitment and satisfaction and follows by the discussion and conceptualization of SDT. The effect of SDT including BSPN and motivational spectrum on commitment and satisfaction will be discussed next. The article shall contribute to the discussion and deliberation on teachers’ motivation, work commitment and satisfaction.